Adenosine A1 Receptor Deficiency Aggravates Extracellular Matrix Accumulation in Diabetic Nephropathy through Disturbance of Peritubular Microenvironment - Dongli Tian; Jiaying Li; Linfeng Zou; Min Lin; Xiaoxiao Shi; Yuting Hu; Jiaxin Lang; Lubin Xu; Wenling Ye; Xuemei Li; Limeng Chen (Journal of Diabetes Research)
Background. We previously observed that adenosine A1 receptor (A1AR) had a protective role in proximal tubular megalin loss associated with albuminuria in diabetic nephropathy (DN). In this study, we aimed to explore the role of A1AR in the fibrosis progression of DN. Methods. We collected DN patients’ samples and established a streptozotocin-induced diabetes model in wild-type (WT) and A1AR-deficient (A1AR-/-) mice. The location and expression of CD34, PDGFRβ, and A1AR were detected in kidney tissue samples from DN patients by immunofluorescent and immunohistochemical staining. We also analyzed the expression of TGFβ, collagen (I, III, and IV), α-SMA, and PDGFRβ using immunohistochemistry in WT and A1AR-/- mice. CD34 and podoplanin expression were analyzed by Western blotting and immunohistochemical staining in mice, respectively. Human renal proximal tubular epithelial cells (HK2) were cultured in medium containing high glucose and A1AR agonist as well as antagonist. Results. In DN patients, the expression of PDGFRβ was higher with the loss of CD34. The location of PDGFRβ and TGFβ was near to each other. The A1AR, which was colocalized with CD34 partly, was also upregulated in DN patients. In WT-DN mice, obvious albuminuria and renal pathological leisure were observed. In A1AR-/- DN mice, more severe renal tubular interstitial fibrosis and more extracellular matrix deposition were observed, with lower CD34 expression and pronounced increase of PDGFRβ. In HK2 cells, high glucose stimulated the epithelial-mesenchymal transition (EMT) process, which was inhibited by A1AR agonist. Conclusion. A1AR played a critical role in protecting the tubulointerstitial fibrosis process in DN by regulation of the peritubular microenvironment.